In Vivo Evolution of Lacticaseibacillus rhamnosus GG Leads to Prolonged Persistence in the Digestive Tract - Alexander Mark; Lorenzo Tosi; Lamia Chkaiban; Raphaela Bento; Biju Parekkadan (Food Bioengineering)
ABSTRACT This study explored in vivo evolution as a method to generate evolutionary clones of Lacticaseibacillus rhamnosus GG, a renowned probiotic organism found in many food supplements, with improved persistence in the intestinal tract. L. rhamnosus GG was autologously gavaged to mice and subsequently selected and grown ex vivo after passage through the intestinal tract to form two evolutionary isolates of the bacteria. A longer retention time (nearly 3×) and a slower elimination rate of the bacteria in the mouse gut were observed with each evolution. The evolutionary isolates were further characterized for key traits such as bile salt resistance, epithelial cell binding, and genetic alterations to understand potential changes to known persistence mechanisms. Finally, a series of heterologous gavages were performed to determine if the increased retention of the evolutionary variants were because of animal‐specific host adaptations. Similar results were seen following heterologous gavages, supporting the concept that intrinsic changes to Lacticaseibacillus occurred. Based on these findings, in vivo evolution shows promise as a technique to generate probiotic strains with improved traits for gut retention as compared to the wild type.